Native Platelet Aggregation and Response to Aspirin in Persons With the Metabolic Syndrome and Its Components - Vaidya, Dhananjay (Mary Ann Liebert, Inc., 2009)
BACKGROUND: Aspirin chemoprophylaxis for coronary artery disease (CAD) is recommended for persons with the metabolic syndrome. We determined the extent to which persons with increased risk for CAD with and without the metabolic syndrome accrued antiplatelet benefits from aspirin therapy. METHODS: We examined 2088 apparently healthy persons with a family history of CAD for the components that comprise metabolic syndrome and classified them according to national guidelines as having the metabolic syndrome or not. We assayed whole blood for ex vivo agonist-induced platelet aggregation (collagen, adenosine diphosphate, and arachidonic acid) and assessed a measure of in vivo platelet activation using urinary 11-dehydrothromboxane B2 (TxM), at baseline and after 2 weeks of treatment with 81 mg/day aspirin. RESULTS: At baseline, in multivariable analyses adjusted for race, age, sex, and risk factors, persons with metabolic syndrome had more aggregable platelets in response to all three agonists and higher levels of TxM (P < 0.005 for all) compared to those without metabolic syndrome. Postaspirin, although all individuals had lower platelet activation measures, subjects with metabolic syndrome retained higher platelet aggregation to adenosine diphosphate (P = 0.002) and higher TxM (P < 0.001), while aggregation to arachidonic acid (P = 0.12) and collagen (P = 0.08) were marginally different between those with and without the metabolic syndrome. CONCLUSIONS: Among persons with an increased risk for CAD, metabolic syndrome was independently associated with overall greater platelet aggregation and activation at baseline and lesser, though significant, effect following aspirin, suggesting that low-dose aspirin therapy alone may not be sufficient to provide optimal anti-platelet protection in persons with metabolic syndrome.